2016
DOI: 10.1515/jeb-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

The Gravity Model Approach: An Application on the Eco Was Trading Bloc

Abstract: This study aims to examine bilateral trade flows across ECOWAS-15 nations with the use of a panel and cross section for the period of 1981-2013. The methodology carried out to achieve this objective involves the use of various techniques of estimation for the gravity model (Static and dynamic). More specifically, this study aims to investigate the formational impact of regional trade integration agreements on trade flows within a group of countries using the same currencies and ECOWAS at large. The main use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…It is notable that the elasticities of the importer's GDP were higher for the exports of manufactured products and machinery and transport equipment, while it was lower for the agricultural exports. Similarly, other studies confirmed from the various regions that the exporter and import GDPs enhance the bilateral exports between members of particular regions (Ekanayake et al, 2010;Luqman et al, 2016;Zainuddin et al, 2020). Contrary to the expectations, the population of exporters and importers exhibited that they are negatively related to various exports in some panels, even though it was insignificant for most of the panels.…”
Section: Gravity Model Estimates Of the Ppml: Regional Groupsmentioning
confidence: 73%
See 2 more Smart Citations
“…It is notable that the elasticities of the importer's GDP were higher for the exports of manufactured products and machinery and transport equipment, while it was lower for the agricultural exports. Similarly, other studies confirmed from the various regions that the exporter and import GDPs enhance the bilateral exports between members of particular regions (Ekanayake et al, 2010;Luqman et al, 2016;Zainuddin et al, 2020). Contrary to the expectations, the population of exporters and importers exhibited that they are negatively related to various exports in some panels, even though it was insignificant for most of the panels.…”
Section: Gravity Model Estimates Of the Ppml: Regional Groupsmentioning
confidence: 73%
“…In addition, it reduces the exports of agricultural products while not significantly affecting the manufactured goods exports for LI and LMI countries. Luqman et al (2016) validated the positive effects of population on trade flows, which demonstrates the domestic market's desire for a variety of products. However, the majority of the literature indicated that there are contradicting impacts of population on bilateral trade flows (Brada & Mendez, 1993;Mátyás, 1997).…”
Section: Gravity Model Estimates Of the Ppml: Income Groupsmentioning
confidence: 77%
See 1 more Smart Citation
“…Luqman et al [10] analyze the structure of bilateral trade and the level of openness of ECOWAS through a gravity model using three techniques: Pseudo Poisson maximum likelihood (PPML), Fully Modified Ordinary Least Squares (FMLOS) and Regression Canonical Cointegration (CCR), for the period from 1981 to 2003. Trade openness was negatively significant under PPML, while financial openness was negatively significant under FMOLS and CCR.…”
Section: Fajimolu and Olayemimentioning
confidence: 99%
“…Afolabi O. Luqman, Nor Aznin Abu Bakar and Azman Aziz Mukhriz Izraf in their study, examined the bilateral trade flow across ECOWAS-15 nations with the use of a panel and cross section for the period of 1981-2013 and investigated the formational impact of regional trade integration agreements on trade flows within a group of countries using the same currencies and ECOWAS at large. They used various techniques of estimation for the gravity model, mainly static and dynamic and the results of their study showed the presence of a strong relationship among the factors of trade flows and regional trade integration agreements [9]. Abdulmenaf Sedjini and Ilirjana Kraja in their paper provided some theoretical and empirical considerations regarding trade development with the focus on export-imports in Albania in relation to the Free Trade Agreements, and applied the gravity model of trade for Albanian case in relation to its 27 export/imports countries.…”
Section: Literature Reviewmentioning
confidence: 99%